Geschichte der Heimat - Oesterhelt, Anja (De Gruyter, 2022)
This study reconstructs the term and concept of “home,” from its traceable origins until the early twentieth century.Literature, here, has acted as a continuous point of reference for the German discursive fields of religion, law, pedagogy, and ethnology: as a medium for the affirmation, confusion, and passing on of social ideas, as well as a site where discourse is constructed and the semantics of home readjusted.